[Economic study on airplane smoking bans] - JOHN LYONS (Tufts Archival Research Center, 2007)
Marginalia; Memorandum from John Lyons to Marty Gleason regarding an economic study on the airplane smoking bans. Suggests allocating money to study the effect the bans have on sales. Claims that several airlines have indicated that if the study shows a drop of even 1%, the airline marketing divisions would appeal to the company to repeal the ban. Points to the larger influence the marketing division has over the company than the government affairs department.